2016
DOI: 10.1002/14651858.cd012325
|View full text |Cite
|
Sign up to set email alerts
|

Fluorine-18-fluorodeoxyglucose (FDG) positron emission tomography (PET) computed tomography (CT) for the detection of bone, lung and lymph node metastases in rhabdomyosarcoma

Abstract: Rhabdomyosarcoma (RMS) is the most common paediatric soft-tissue sarcoma and can emerge throughout the whole body. For patients with newly diagnosed RMS, prognosis for survival depends on multiple factors such as histology, tumour site, and extent of the disease. Patients with metastatic disease at diagnosis have impaired prognosis compared to those with localised disease. Appropriate staging at diagnosis therefore plays an important role in choosing the right treatment regimen for an individual patient. Fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
0
1
Order By: Relevance
“…Based on the imaging of DWI, our results showed that the incidence of medial group RLNs was nearly 3%, which was much higher than previous studies (31). Among DWI, T2 STIR and enhanced CT, the sensitivity of DWI is least affected by the size of lymph nodes, rendering DWI an advantage in detecting small lymph nodes.…”
Section: Discussioncontrasting
confidence: 50%
“…Based on the imaging of DWI, our results showed that the incidence of medial group RLNs was nearly 3%, which was much higher than previous studies (31). Among DWI, T2 STIR and enhanced CT, the sensitivity of DWI is least affected by the size of lymph nodes, rendering DWI an advantage in detecting small lymph nodes.…”
Section: Discussioncontrasting
confidence: 50%